Graphene‐Based Intrinsically Stretchable 2D‐Contact Electrodes for Highly Efficient Organic Light‐Emitting Diodes (Adv. Mater. 31/2022). Issue 31 (4th August 2022) - Zhou, Huanyu; Han, Shin Jung; Harit, Amit Kumar; Kim, Dong Hyun; Kim, Dae Yoon; Choi, Yong Seok; Kwon, Hyeokjun; Kim, Kwan‐Nyeong; Go, Gyeong‐Tak; Yun, Hyung Joong; Hong, Byung Hee; Suh, Min Chul; et al.
Abstract : Organic Light‐Emitting Diodes Intrinsically stretchable light‐emitting diodes (ISOLEDs) are becoming increasingly important for wearable electronics. In article number 2203040, Han‐Young Woo, Tae‐Woo Lee, and co‐workers report the design of highly efficient ISOLEDs that use a graphene‐based 2D‐contact stretchable electrode. As a benefit of a newly designed conjugated polyelectrolyte with efficient electron injection capability, the ISOLED yields an unprecedently high current efficiency of 20.3 cd A −1 .